Prediksi Jumlah Tunggakan Pembayaran Rekening Air Menggunakan Metode Least Square - Abd Rahmat karim Haba (Teknik Elektro - Universitas Ichsan Gorontalo, 2021)
PDAM is committed to providing the best service for Gorontalo, but there are obstacles, namely the condition of arrears in payment of water bills fluctuating or fluctuating. The purpose of this research is to design a prediction system for water payment arrears. This study uses the least square method in predicting arrears in water bill payments at PDAM Muara Tirta, Gorontalo City. The results show that the prediction of the amount of water payment arrears using the Least Square method is feasible to use. The value of the MAPE test results is 6.70% with an accuracy of 93.3%.